Sustainable livestock management for poverty alleviation and food security [ - Hooft, Katrien van't , 1956-; Bhandari, Dilip P.; Wollen, Terry S. (CABI, 2012)
Good animal husbandry practices and animal health are vital for people living in poorer countries. This guide is suitable for those responsible for training farmers in poor countries, taking into account traditional farming systems, existing inputs and esources, sustainable farming initiatives and advising on the right approaches to training